1983
DOI: 10.1111/j.1464-410x.1983.tb03290.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration Cytology of Solid Renal Tumours

Abstract: The results of needle aspiration cytology of solid renal lesions in Brighton from 1977 have been reviewed. Thirty-one lesions were aspirated and of the 21 malignant tumours, cytology accurately diagnosed 19 (90%) when sufficient material was sent for analysis. Of the eight avascular solid renal space-occupying lesions aspirated, cytology gave a correct differentiation (benign versus malignant) in seven (87%). The results compare favourably with those of other published experience. A modification is suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

1985
1985
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 11 publications
0
22
1
Order By: Relevance
“…2,6 The majority of cysts are benign, acquired, and soli-( In most series with histologic follow-up, radiographically suspicious cysts almost always prove to be RCC. 4,7,10 Finally, in the largest series of cystic RCCs to date (11 cases), only 2 cases had atypical cells on cytologic examination, and repeated aspirates in these 2 patients were negative. 44 This strongly suggests that the sensitivity of FNA for the diagnosis of cystic RCC is low, and will remain so despite attempts to thoroughly sample the edge of radiographically cystic lesions.…”
Section: Cystic Lesionsmentioning
confidence: 95%
See 1 more Smart Citation
“…2,6 The majority of cysts are benign, acquired, and soli-( In most series with histologic follow-up, radiographically suspicious cysts almost always prove to be RCC. 4,7,10 Finally, in the largest series of cystic RCCs to date (11 cases), only 2 cases had atypical cells on cytologic examination, and repeated aspirates in these 2 patients were negative. 44 This strongly suggests that the sensitivity of FNA for the diagnosis of cystic RCC is low, and will remain so despite attempts to thoroughly sample the edge of radiographically cystic lesions.…”
Section: Cystic Lesionsmentioning
confidence: 95%
“…The authors believe that cytopathologists must ses. 3,7,43 The appearance of the metastasis depends on the be able to identify benign lesions, and also grade and primary tumor. However, in general, in contrast to RCC, subtype RCCs.…”
Section: Papanicolaou Stain)mentioning
confidence: 99%
“…10,15,32 However, despite substantial literature describing the cytologic features of various RCC subtypes, the reliability of these criteria in distinguishing these subtypes from each other has not been assessed. Some of the features we think are most useful are listed in Table II.…”
mentioning
confidence: 99%
“…Some authors suggested to per form FNAC as a routine procedure when ultrasound revealed a solid renal mass [9,10]. If the radiological diag nosis is not clear, one should keep in mind that the major ity of solid hypovascular renal lesions are malignant.…”
Section: Commentsmentioning
confidence: 99%
“…It is inserted into the tumor under CT or ultra sound guidance, and viable tumor cells are aspirated, preferentially from the periphery of the tumor, since the central part often contains only necrotic cells [9,10].…”
Section: Commentsmentioning
confidence: 99%